Factors Affecting The Knowledge Of Pregnant Women In The Third Trimester About Red Ginger Drinks As a Pain Reliever For First Stage Of Labor in The Active Phase Of The Regional General Hospital Of Perdagangan, Simalungun Regency In 2024 - Srilina Br Pinem; Murni Sari Dewi; Herna Rinayanti Manurung; Dyanti Butar-Butar; Adelina Sembiring; Rumondang Sitorus; Ester Simanulang (International Journal of Health and Medicine, 2025)
Labor pain during the first stage of active phase is visceral, arising from uterine contractions and cervical dilation, processed through sympathetic efferent nerve fibers. One therapy that can be used to reduce this pain is the administration of red ginger extract, which is known to have the highest oleoresin content compared to other types of ginger. This study aims to assess the factors influencing the knowledge of third-trimester pregnant women about the benefits of red ginger drink as a pain reliever during the first stage of active labor at the RSUD Daerah Perdagangan. The study used an analytic cross-sectional design involving 66 respondents who met specific inclusion and exclusion criteria. The results showed that education, age, received information, and culture influenced pregnant women’s knowledge about the benefits of red ginger. Based on statistical tests, it was found that education, age, information, and culture have a significant impact on the level of knowledge among pregnant women. This study is expected to contribute to increasing pregnant women’s knowledge of alternative pain relief methods using red ginger and to enrich awareness of the importance of health information during pregnancy.